Egodystonic Homosexuals In Heterosexual Marriages (A Study Of Christian Discourse) - Irene Oktadiana Setijo; Amin Budiasih; Hudi Winarso (Jurnal Indonesia Sosial Teknologi, 2023)
Egodystonic type homosexuality is a condition where the individual has internal conflicts over his homosexual behavior. Therefore, not a few egodystonic homosexuals hide their sexual orientation by marrying the opposite sex, which we call heterosexual marriage. This study aims to analyze homosexuals engaged in heterosexual marriage, and the effect on their marital life. This study also analyzes the Christian view of homosexuals who are involved in heterosexual marriages. The result of this study is that humans were created as heterosexual beings, starting with the creation of Adam and Eve. The purpose of creating two sexes is to execute the reproductive function and for humans to not fall into sexual sin. In Christian’s view, it is stated that homosexual relationship is an abomination and forbidden. Marriage in Christianity is a sacred covenant before God. Homosexuals who engage in heterosexual marriages will have lots of conflicts, including having problems with themselves and their partners. Homosexuals in heterosexual marriage are recommended to take intensive consultation with marriage counselors, for marital happiness.